(De)constructing “America”: the Case of Emir Kusturica’s Arizona Dream (1993) - David Roche (European Journal of American Studies)
By means of an analysis of Kusturica’s only film about America, Arizona Dream, this article argues that while the United States offers a vision of a united society founded on diversity, it also represses, altering in the process both society and the landscape. National unity is consequently a dream – a dream the film suggests that has often been dreamed up by un-Americans. Filtered through Kusturica’s own perceptions of America – and his position on the Balkan War (1991-2001) – the film seems to suggest sadness at the loss of a multi-ethnic, multi-cultural perspective. Through its representations of geography and ethnic diversity, and its dense network of filmic citations, what Arizona Dream ultimately offers is consequently a European auteur’s view of the United States rather than a systematic deconstruction of the “imagined community” of “America.”